2014
DOI: 10.5216/cab.v15i1.20144
|View full text |Cite
|
Sign up to set email alerts
|

Alterações No Hemograma De Cadelas Com Neoplasia Mamária

Abstract: As alterações no hemograma estão direta ou indiretamente relacionadas com câncer e são pouco descritas em cadelas com neoplasia mamária. O objetivo deste estudo foi analisar as alterações hematológicas em 161 cadelas portadoras de neoplasia mamária e correlacionar à progressão da doença. As principais alterações hematológicas encontradas foram anemia normocítica e normocrômica e leucocitose neutrofílica, sendo ambas mais frequentes em cadelas em estádio avançado (III, IV ou V) da doença.Conclui-se que as alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
1
6
0
11
Order By: Relevance
“…In addition, microangiopathic hemolytic anemia and immune-mediated hemolytic anemia have already been described in mammary carcinoma (Mangieri 2009); however, the most relevant cause of nonregenerative anemia in cancer patients is believed to be anemia of chronic disease, also known as anemia of inflammation (Childress 2012). There are few studies that evaluate the association of hematological condition with mammary neoplasm, but the results are similar, considering that normocytic, normochromic anemia was previously observed in 11.2% (11/161) of dogs (Silva et al 2014), whereas another study only indicated a reduction in erythrocyte levels in bitches with mammary carcinoma compared with a control group (Estrela-Lima et al 2012). …”
Section: Discussionmentioning
confidence: 78%
“…In addition, microangiopathic hemolytic anemia and immune-mediated hemolytic anemia have already been described in mammary carcinoma (Mangieri 2009); however, the most relevant cause of nonregenerative anemia in cancer patients is believed to be anemia of chronic disease, also known as anemia of inflammation (Childress 2012). There are few studies that evaluate the association of hematological condition with mammary neoplasm, but the results are similar, considering that normocytic, normochromic anemia was previously observed in 11.2% (11/161) of dogs (Silva et al 2014), whereas another study only indicated a reduction in erythrocyte levels in bitches with mammary carcinoma compared with a control group (Estrela-Lima et al 2012). …”
Section: Discussionmentioning
confidence: 78%
“…Resultados diferentes foram observados por Silva et al (2014) que encontraram alterações em 24,2% dos pacientes (39/161), sendo 18 animais com alterações no eritrograma e 30 no leucograma.…”
Section: Resultado E Discussãounclassified
“…As características clínicas encontradas durante a realização do experimento foram que as cadelas atendidas apresentavam média de idade de 9,85 (+2,3) anos, muito próximo a pesquisa de Oliveira et al (2003) que encontraram média de idade de 9 (+3,1) anos e a maioria eram cães sem raça definida. Também Silva et al (2014), encontraram em seu estudo uma idade média de 10,1 anos (5-17). Referente à raça a maioria das cadelas atendidas pela pesquisa foi SRD (sem raça definida), o que correspondeu a 15 cadelas (80%).…”
Section: Discussionunclassified
“…Nos exames pré-operatórios a única alteração constatada na pesquisa foi leucocitose por neutrofilia em 9 cadelas (45%). Este resultado encontra-se superior ao encontrado por Silva et al (2014), que em seu estudo constataram leucocitose neutrofílica em 18,6% das pacientes. A leucocitose por neutrofilia verificada neste trabalho possivelmente reflete a condição inflamatória decorrente da neoplasia mamária, e também à ulceração presente em algumas pacientes (Childress 2012).…”
Section: Discussionunclassified